IMPACT OF VARIABLE FREQUENCY DRIVE ON THE EFFICIENCY OF CENTRIFUGAL PUMPS IN OIL PIPELINE UNITS - Лагойда, Андрій; Костишин, Андрій; Лагойда, Людмила; Костишин, Сергій (SWorldJournal, 2023)
The article examines the impact of implementing a variable frequency drive on the efficiency of centrifugal pumps in oil pipeline unit systems. Various methods of regulating the operational process and their influence on power consumption and fluid flow